The contribution of reticular basement membrane proteins to basal airway epithelial attachment, spreading and barrier formation: implications for airway remodeling in asthma - Hsieh, Aileen; Yang, Chen Xi; Al-Fouadi, May; Nwozor, Kingsley Okechukwu; Osei, Emmanuel Twumasi; Hackett, Tillie-Louise (Frontiers in Medicine, 2023)
Rationale: In the healthy lung, the pseudostratified conducting airway epithelium is anchored to the reticular basement membrane (RBM) via hemidesmosome junction complexes formed between basal cells and the extracellular matrix (ECM). The RBM within the healthy lung is composed of the ECM proteins laminin and collagen IV. In patients with asthma, the RBM is remodelled with collagen-I, -III and fibronectin deposition. The goal of this study was to assess the effect of RBM ECM proteins on basal airway epithelial cell attachment, spreading and barrier formation using real-time electrical cell-substrate impedance sensing (ECIS).Methods: ECIS 8-well arrays were coated with 50µg/ml of fibronectin, collagen-I, collagen-III, collagen-IV, or laminin and compared to bovine serum albumin (BSA) or uncoated controls. The airway epithelial cell line (1HAEo-) was seeded 40k, 50k, 60k and 70k/well and continuously monitored over 70hrs to assess cell attachment, spreading and barrier formation using high (64k Hz) and low (500Hz) frequency resistance and capacitance. Data were analysed using one-phase decay model from which half-life (time cells cover half of the electrode area) and rate-constant (cell-spreading rate/hr) were determined and a generalized additive mixed effect model (GAMM) was used to assess ECM proteins over the entire experiment.Results: High-frequency (64kHz) capacitance measures demonstrated the half-life for 1HAEocells to attach was fastest when grown on fibronectin (6.5hrs), followed by Collagen-I (7.2hrs) and collagen-III (8.1hrs), compared to collagen IV (11.3hrs), then laminin (13.2hrs) compared to BSA (12.4hrs) and uncoated (13.9hrs) controls. High-frequency (64kHz) resistance measures demonstrated that the rate of 1HAEo-cell spreading was significantly faster on fibronectin and collagen-I compared to Collagen-III, collagen-IV, Laminin, BSA and the uncoated control. Lowfrequency (500 Hz) resistance measures demonstrated that 1HAEo-cells formed a function barrier fastest when grown on fibronectin and collagen-I, compared to the other ECM conditions.Lastly, the distance of 1HAEo-cells from the ECM substrates was the smallest when grown on fibronectin reflecting high cell-matrix adhesion.Conclusions: Airway epithelial cells attach, spread and form a barrier fastest on fibronectin, and collagen I and these reticular basement membrane ECM proteins may play a protective role in preserving the epithelial barrier during airway remodelling in asthma